2021
DOI: 10.3390/foods10071531
|View full text |Cite
|
Sign up to set email alerts
|

Skin Color Retention in Red Potatoes during Long-Term Storage with Edible Coatings

Abstract: In this study, we aimed to investigate the effect of edible coatings and cold storage conditions on the skin color of red potatoes (Ciklamen and Modoc) stored for six months at 4 ± 2 °C and 90 ± 5% relative humidity (RH). The four different formulations used were sodium alginate (F1), sodium alginate and potato starch (F2), zein and chitosan (F3), and chitosan, sodium alginate and potato starch (F4), in addition to the control treatment with distilled water. The treated samples were assessed periodically durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The results of this study are in accordance with the results of similar studies that observed an increase in formed pigments in food products during storage [33]. Similar results were obtained when coatings of sodium alginate and potato starch were applied to red potato samples and observed that the values of the Chroma* parameter increased compared to samples of the Ctr treatment [58]. These differences were characterized as significant.…”
Section: Texture Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are in accordance with the results of similar studies that observed an increase in formed pigments in food products during storage [33]. Similar results were obtained when coatings of sodium alginate and potato starch were applied to red potato samples and observed that the values of the Chroma* parameter increased compared to samples of the Ctr treatment [58]. These differences were characterized as significant.…”
Section: Texture Analysissupporting
confidence: 91%
“…The degradation of starch granules occurs due to the increase in the activity of αamylase, which hydrolyzes the α-glycosidic bonds of starch [32,57]. Moreover, it was found that starch granules stored for a long period of time undergo degradation [58]. Therefore, the storage of Colocasia samples in different storage environments may lead to changes in the physicochemical properties of its flour and starch due to the activity of temperature-sensitive α-amylase.…”
Section: Texture Analysismentioning
confidence: 99%
“…For example, chitosan with whey protein and coconut oil (lipid) on the shelf life of potato, 90 and zein, chitosan, sodium alginate, and potato starch to retain the anthocyanin content in red potato. 91 The different combination approaches of these coating may also discover the potential to reduce greening.…”
Section: And Tga In Potatomentioning
confidence: 99%
“…Researchers have successfully applied edible coating on the potato to solve various problems except greening because of the limitations due to food safety. For example, chitosan with whey protein and coconut oil (lipid) on the shelf life of potato, and zein, chitosan, sodium alginate, and potato starch to retain the anthocyanin content in red potato . The different combination approaches of these coating may also discover the potential to reduce greening.…”
Section: Postharvest Factors Affecting Greening and Tga In Potatomentioning
confidence: 99%
“…This issue has led to the development of CIS-resistant potatoes for the snack (chip) industry [16,17]. Likewise, cold storage has been shown to promote the accumulation of antioxidant compounds in some cases such as total phenolics [18] and anthocyanins [19], and other works have shown that the effect of cold storage strongly depends on the cultivar and growing conditions [20,21].…”
Section: Introductionmentioning
confidence: 99%